Effects of Friction Plate Hardness and Surface Orientation on the Frictional Properties of Cereal Grain - Zdzisław Kaliniewicz; Krzysztof Jadwisieńczak; Zbigniew Żuk; Stanisław Konopka; Adam Frączyk; Zbigniew Krzysiak (International Journal of Food Science)
The objective of this study was to evaluate the effects of the friction plate hardness and surface orientation of a friction plate on the angle and coefficient of static friction of cereal kernels. The angle of static friction of kernels representing four major cereal species was measured on six friction plates with different hardness. The friction plates were placed in position where their surface orientation was perpendicular or parallel relative to their inclination tilt. The experimental material comprised the so-called flat seed units, where each unit consisted of three spaced kernels. The angle of static friction of every flat seed unit was measured with a dedicated device in three replications, and average values of that angle were calculated. The kernels’ angle of static friction varied considerably from 13° to 33° within the analyzed range of changes in the surface characteristics of friction plates. The average angle of static friction was influenced mainly by the surface orientation of the friction plate that came into contact with cereal kernels. The angle of static friction was 17.5% to 56.5% higher when the friction plate had perpendicular rather than parallel surface orientation. The frictional properties of kernels were less influenced by plate hardness, and clear relationships were not observed in this respect. The kernels’ coefficient of static friction remained fairly constant within the analyzed range of plate hardness values, and it was estimated at 0.4 on plates with a perpendicular surface orientation and at 0.3 on plates with a parallel surface orientation.